Peritoneal flap for lymphocele prophylaxis following robotic-assisted laparoscopic radical prostatectomy with pelvic lymph node dissection: study protocol and trial update for the randomized controlled PELYCAN study - Neuberger, Manuel; Kowalewski, Karl-Friedrich; Simon, Valentin; Wessels, Frederik; Siegel, Fabian; Worst, Thomas; Westhoff, Niklas Christian; Hardenberg, Jost von; Kriegmair, Maximilian; Michel, Maurice Stephan; Honeck, Patrick; Nuhn, Philipp (Trials, 2021)
Data from interventional studies suggest that a peritoneal flap after pelvic lymph node dissection (LND) during laparoscopic, robotic-assisted radical prostatectomy (RARP) may reduce the rate of symptomatic lymphoceles in transperitoneal approach. However, most of these studies are not conducted in a randomized controlled fashion, thus limiting their scientific value. A recent prospective, randomized, controlled trial (RCT) did not show superiority of a peritoneal flap while further trials are lacking. Therefore, the aim of the presented RCT will be to show that creating a peritoneal flap decreases the rate of symptomatic lymphoceles compared to the current standard procedure without creation of a flap.
Gesehen am 03.08.2021